Equivalence Analysis of Mass and Inertia for Simulated Space Manipulator Based on Constant Mass - Sihui Tian; Xiaoqiang Tang; Chengyuan Xiang (Machines, 2017)
A simulated space manipulator is designed to verify the reliability of the zero-gravity simulation system, which can avoid the risks of experiments involving the space manipulator in this zero-gravity ground system. To achieve similarity between the simulated and actual space manipulators, the mass, barycenter, and inertia must be considered. In this study, a counterweight component is designed and an optimization method is used to match the mass parameters of the simulated joints to those of the space joints. In addition, an equivalence method is used to establish the relationship between the torques of these two manipulators.